Reliability of real-time ultrasound measurement of transversus abdominis thickness in healthy trained subjects - Gnat, Rafael (Springer-Verlag, 2012)
PURPOSE: To investigate intra- and inter-rater reliability of the ultrasound measurement of transversus abdominis (TrA) thickness and thickness change (difference between thickness at rest and during contraction) in asymptomatic, trained subjects. To define the number of repeated measurements that provide acceptable level of reliability. To investigate variability of the measurements over time of 5 days and the reliability of duplicate analysis of images. METHODS: A single-group repeated-measures design was used to assess reliability. Healthy volunteers (n = 10) were subjected to 1-week training in voluntary activation of TrA. Real-time ultrasound imaging and subsequent measurement of the TrA thickness at rest and during voluntary contraction were repeated on Monday, Wednesday and Friday of the next week. RESULTS: Using a single repeated measurement, intraclass correlation coefficients (ICCs) for TrA thickness were: 0.86–0.95 (intra-rater), 0.86–0.92 (inter-rater); and for TrA thickness change: 0.34–0.56 (intra-rater), 0.47–0.61 (inter-rater). Using the mean of three repeated measurements respective values were: 0.97, 0.96–0.98; and 0.81–0.84, 0.80–0.90. No significant differences were found between mean values of TrA thickness as well as thickness change obtained on three consecutive measurement days. Duplicate analysis of the images was highly reliable with ICCs of 0.89–0.99. CONCLUSIONS: Two repeated measurements for TrA thickness and at least three measurements for TrA thickness change are needed to achieve acceptable levels of intra- and inter-rater reliability. In healthy trained volunteers TrA thickness and thickness change are relatively stable parameters over a 5-day period. Duplicate analysis of the same images by two blinded observers is reliable.